Biosynthesis of the methanogenic cofactors - White, Robert H (Cofactor Biosynthesis: a Mechanistic Perspective, 2001)
Our current knowledge of the pathways and genes involved in the biosynthesis of the methanogenic coenzymes methanopterin, coenzyme B, methanofuran, coenzyme F 420, and coenzyme M is presented. Proposed reaction mechanisms for several of the novel reactions involved in the pathways are presented.